Bavachin Protects Human Aortic Smooth Muscle Cells Against β-Glycerophosphate-Mediated Vascular Calcification and Apoptosis via Activation of mTOR-Dependent Autophagy and Suppression of β-Catenin Signaling - He, Hu-Qiang; Law, Betty Yuen Kwan; Zhang, Ni; Qiu, Cong-ling; Qu, Yuan-Qing; Wu, An-Guo; Han, Yu; Song, Qi; Zheng, Wen-Lu; Liu, Yong; He, Yan-Zheng; Wong, Vincent Kam Wai (Frontiers in Pharmacology, 2019)
Abstract Vascular calcification is a major complication of cardiovascular disease and chronic renal failure. Autophagy help to maintain a stable internal and external environment that is important for modulating arteriosclerosis, but its underlying mechanism is still unclear. In this study, we aimed to identify the bioactive compounds from traditional Chinese medicines (TCM) that exhibit an anti-arteriosclerosis effect. In β-glycerophosphate (β-GP)-stimulated human aortic smooth muscle cells (HASMCs), the calcium level was increased and the expression of the calcification-related proteins OPG, OPN, Runx2, and BMP2 were all up-regulated, followed by autophagy induction and apoptosis. Meanwhile, we further revealed that β-GP induced apoptosis and promoted osteogenic differentiation of human osteoblastic cells via Wnt/β-Catenin signaling. Bavachin, a natural compound from Psoralea corylifolia, dose-dependently reduced the level of intracellular calcium and the expression of calcification-related proteins OPG, OPN, Runx2 and BMP2, thus inhibiting cell apoptosis. In addition, Bavachin increased LC3-II and beclin1 expression, along with intracellular LC3-II puncta formation, which autophagy induction is Atg7-dependent and is regulated by suppression of mTOR signaling. Furthermore, addition of autophagy inhibitor, wortmannin (WM) attenuated the inhibitory effect of Bavachin on β-GP-induced calcification and apoptosis in HASMCs. Collectively, the present study revealed that Bavachin protects HASMCs against apoptosis and calcification by activation of the Atg7/mTOR‐autophagy pathway and suppression of the Wnt/β-catenin signaling, our findings provide a potential clinical application for Bavachin in the therapy of cardiovascular disease.